Case of “Slow” Stroke from Carotid Artery Occlusion Treated by Delayed but Cautious Endovascular Intervention - Kachi Illoh; Emilio Supsupin; Hashem M. Shaltoni; Edwin D. Cacayorin (Stroke Research and Treatment)
In a challenging case of carotid occlusion with slowly evolving stroke, we used brain imaging to facilitate endovascular revascularization resulting in the relief of the patient's symptoms. Patients with carotid occlusion and continued neurological worsening or fluctuations present enormous treatment challenges. These patients may present “slow” strokes with subacute infarcts that present significant challenges and risks during attempts at revascularization of the occluded artery. We present such a case in which we used multimodal imaging techniques, including MR-perfusion, to facilitate endovascular revascularization. Our approach of delayed but cautious intra-arterial thrombolytic therapy, guided by brain imaging, and followed by stent placement across the residual stenosis, enabled revascularization of the occluded artery without overt in-hospital complications.